2023
DOI: 10.3389/ffgc.2022.1086328
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon, nitrogen, and phosphorus stoichiometry and its influencing factors in Chinese fir plantations across subtropical China

Abstract: The crucial roles of soil carbon (C) and nutrients and their stoichiometric characteristics in indicating the soil interior nutrient cycling and plant nutrient supply of forest ecosystems have been widely verified, whereas it has been less explored when considering the influencing factors regionally, especially for the widely cultivated plantation tree species. In the current study, the patterns of soil organic C (SOC), total nitrogen (TN), and total phosphorus (TP) stoichiometry in Chinese fir [Cunninghamia l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
5
1
Order By: Relevance
“…Sheng et al (2022) also founded that soil C:N was positively correlated with elevation in paddy soils. For latitude, consistent results suggested that the lowest soil C:N values were found at higher latitude (Feng et al, 2017;Tong et al, 2023). However, Fang et al (2019) found that there was no significant correlation between soil C:N and latitude in the Loess Plateau, which is inconsistent with our findings.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Sheng et al (2022) also founded that soil C:N was positively correlated with elevation in paddy soils. For latitude, consistent results suggested that the lowest soil C:N values were found at higher latitude (Feng et al, 2017;Tong et al, 2023). However, Fang et al (2019) found that there was no significant correlation between soil C:N and latitude in the Loess Plateau, which is inconsistent with our findings.…”
Section: Discussioncontrasting
confidence: 81%
“…However, the formation of phosphorus in soil is mainly related to the parent material and bedrock minerals. Consequently, there is usually a tight coupling relationship between SOC and TN, which is not common between SOC and TN as well as between TN and TP (Tong et al, 2023). Older studies also have reported that the coupling relationship between C and nutrients occurred in karst forest soil during forest restoration (Yu and Chi, 2020;Lu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observed outcome highlights the importance of nutrient management strategies that integrate organic inputs such as Azolla and rice straw and the synergy between organic amendments and adjusted synthetic fertilizers contributes to the improvement of SOC, indicating a more sustainable and holistic approach to soil health. Soil organic carbon along with their stoichiometric characteristics, are important indicators for the quality and quantity of soil organic matter (104). The carbon-to-nitrogen (C:N) ratio in the soil is a crucial indicator of nutrient availability and microbial activity (105).…”
Section: Effects Of Treatment Combinations On Soil Chemical Propertiesmentioning
confidence: 99%
“…Additionally, several factors, such as pH, soil parent material, management practices, and climate change, influence P fractions and solubility of phosphorus (Azene et al, 2022). Phosphorus may be present in soil parent materials in relatively high amounts, yet more than 80% gets fixed as immobile stock and a fraction of P that is available to plant does not exceed 15%-20% (van de Wiel et al, 2016;Biswas Chowdhury and Zhang, 2021;Jiang et al, 2021). Previous studies demonstrated that fertilization of P into soil results in its distribution among the solid phase and clay-sized minerals.…”
Section: Introductionmentioning
confidence: 99%